Quando a prisão é prisão mesmo: gestão privada e humanização do cárcere em Sergipe - Santana, Aline Passos de Jesus (2021)
This work is about the private management of a prison unit in Sergipe. Through ethnographic research, document analysis, and on-site observation, we sought to understand the routine and procedures implemented by a private company in a disciplinary institution traditionally administered by the State. One of the research objectives was to understand whether the transition from State to private management resulted in improvement or deterioration of the prison's environment, since the public debate on prisons revolves around their humanization through reforms and managerial indicators regarding food, medical care, hygiene of the facilities, among others. Another objective was to analyze the relationships between public and private managers in a co-management regime that assigns, to the former, the functions of direction and inspection, and to the latter, the execution of ordinary services. One of the findings is that the improvement of environmental conditions carried out by the private sector is accompanied by the intensification of surveillance and control devices for the activities of prisoners, so that the humanization of prisons was compatible with privatization and the expansion of the prison system in Sergipe.